Incidence and risk factors of hyperemesis gravidarum: A national register‐based study in Finland, 2005–2017 - Miina Nurmi; Päivi Rautava; Mika Gissler; Tero Vahlberg; Päivi Polo‐Kantola (WILEY, 2022)
Introduction
Hyperemesis gravidarum is the most common reason for hospitalization in early pregnancy in pregnancies resulting in delivery. Several associative factors indicate that the etiology is likely to be multifactorial. To assess this, we used a unique procedure to compare hyperemetic pregnancies to non‐hyperemetic pregnancies both with different women and the same women's different pregnancies.
Material and methods
Data about all pregnancies resulting in delivery in Finland in 2005–2017 were retrieved from health care registers. Women who had hyperemesis gravidarum diagnosis in any pregnancy in the Finnish Hospital Discharge Register were chosen as cases (n = 9315) and other women (n = 428 150) as the reference group. Incidence of hyperemesis gravidarum was calculated and associations between hyperemesis and maternal, environmental and pregnancy‐related factors were analyzed in a novel setting by comparing case women's pregnancies diagnosed with hyperemesis to 1) reference group women's pregnancies and 2) case women's non‐hyperemetic pregnancies.
Results
Out of the 437 465 women who had at least one pregnancy resulting in delivery during the study period, 9315 women had at least one hyperemetic pregnancy. Total number of pregnancies resulting in delivery was 741 387 and 9549 of those were diagnosed with hyperemesis gravidarum, thus the incidence of hyperemesis gravidarum was 1.3%. In comparison 1), case women's hyperemetic pregnancies vs reference group's pregnancies, younger maternal age, higher gravidity, underweight and overweight were associated with increased risk of hyperemesis; in contrast, in comparison 2), case women's hyperemetic pregnancies vs their non‐hyperemetic pregnancies, higher age and obesity were associated with higher risk of hyperemesis, whereas the risk was lower as gravidity and parity increased. In both comparisons, smoking was associated with lower risk, whereas higher municipality population, assisted reproductive technology, multiple gestation and female sex of the fetus were associated with increased risk of hyperemesis.
Conclusions
​​​​​​​
Our novel study setting provided new insights about risk factors: hyperemetic pregnancies differ both from pregnancies of women who had never been diagnosed with hyperemesis and from hyperemetic women's non‐hyperemetic pregnancies. Incidence of hyperemesis gravidarum in Finland was comparable to other countries.